Eficacia de enmienda y aminoácidos sobre el crecimiento y rendimiento de plántulas de fréjol caupí (Vigna unguiculata) en suelo de tendencia salina - Falcones Párraga, Alicia Mercedes (2022)
The objective of the research was to evaluate the efficacy of amendments and amino acids on the growth and yield of cowpea bean (Vigna unguiculata) seedlings in saline-prone soil. The experiment was carried out under shady conditions at the ESPAM MFL polytechnic campus. Two trials separated in time were developed. In the first, three doses of gypsum - GY (14, 28 and 42 g per pot) and three doses of compost - CP (14, 28 and 42 g per pot) were evaluated. In the second trial, three sources of amino acids (vegetable, marine and animal origin) were evaluated. As an amendment, the best combination of GY + CP obtained in the first experiment was used. In both experiments, the dry weight of plants and grain yield per plant were recorded. The data obtained were analyzed through ANOVA, orthogonal contrast and the separation of means was carried out with the Tukey test (α = 0.05). No significant differences (p>0.05) were found for the GY x CP interaction, nor for the simple effects of YA and CP. The orthogonal contrast between the averages of YA+CP vs. the control, did show significant differences (p<0.05), so it is concluded that the minimum doses of YA and CP are sufficient to enhance the growth and yield of cowpea bean seedlings in saline-prone soil. The second experiment did find significant differences (p<0.05) between treatments, where the amino acids, regardless of their origin, contributed to improving the growth and yield of the cowpea bean